2019
DOI: 10.1038/s41598-018-37675-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-step isolation of carbon nanotubes with narrow-band light emission characteristics

Abstract: Lack of necessary degree of control over carbon nanotube (CNT) structure has remained a major impediment factor for making significant advances using this material since it was discovered. Recently, a wide range of promising sorting methods emerged as an antidote to this problem, all of which unfortunately have a multistep nature. Here we report that desired type of CNTs can be targeted and isolated in a single step using modified aqueous two-phase extraction. We achieve this by introducing hydration modulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Biphasic separation without chemical modulators. We started the study by conducting a differentiation of SWCNT in the absence of basic salts by using the previously determined starting parameters 30 . As can be seen, these conditions already gave somewhat preliminary separation of CNTs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Biphasic separation without chemical modulators. We started the study by conducting a differentiation of SWCNT in the absence of basic salts by using the previously determined starting parameters 30 . As can be seen, these conditions already gave somewhat preliminary separation of CNTs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we observed that higher resolution may be obtained upon the addition of ammonia 30 . However, we noticed that over time the change in ammonia water concentration might hurt the result of ATPE separation of CNTs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different strategies with respect to isolation of puried populations have also been reported; in my lab we tend to apply generalized processing workows to make several separations with the goal to collect pure, or enriched populations of all (n,m) structures present. Other groups have reported optimized short step routes to isolate specic (n,m) structures, [26][27][28] but with the typical cost for such simplication being that all other species are aggregated and discarded. Both strategies can be useful given time constraints and the easier adoption and dissemination of recipe methods, and will be described in more detail in the next section.…”
Section: Introductionmentioning
confidence: 99%